Credit Risk and Credit Rationing: A Reply - Hodgman, Donald R. (Quarterly Journal of Economics, 1961)
Journal Article The Use of Adaptive Expectations in Stability Analysis: Reply Get access Donald R. Hodgman Donald R. Hodgman University of Illinois Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 75, Issue 2, May 1961, Pages 327–329, https://doi.org/10.2307/1884207 Published: 01 May 1961